Acupuncture for Chronic Obstructive Pulmonary Disease: A 38-Year Bibliometric Landscape of Global Research Trends and Knowledge Evolution (1986–2024) - Wu K; Ruan C (International Journal of COPD, 2025)
Kaiting Wu,1 Chen Ruan2 1Medical Comprehensive Ward, Xianlin Campus, Tongde Hospital of Zhejiang Province, Hangzhou, Zhejiang, People’s Republic of China; 2Acupuncture Department, Cuiyuan Campus, Tongde Hospital of Zhejiang Province, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Chen Ruan, Acupuncture Department, Cuiyuan Campus, Tongde Hospital of Zhejiang Province, Hangzhou, Zhejiang, 310012, People’s Republic of China, Email 15967121022@163.comBackground: Despite growing interest in acupuncture as a complementary therapy for chronic obstructive pulmonary disease (COPD), comprehensive analyses of its global research trajectory, disciplinary convergence patterns, and geopolitical contributions remain unexplored. This study addresses this gap by mapping the intellectual and geopolitical architecture of acupuncture-COPD research over nearly four decades, a period chosen to capture the significant developments in acupuncture’s global recognition since the late 1980s, when traditional medicine began to gain more global attention.Methods: We conducted a longitudinal bibliometric analysis of 299 publications indexed in the Web of Science Core Collection (1986– 2024). Employing Bradford’s and Lotka’s laws, co-citation networks, and keyword co-occurrence clustering, we systematically evaluated temporal productivity trends, institutional/country contributions, citation dynamics, and thematic evolution using SciMAT, VOSviewer, and bibliometrix R-package. (Response to Editor’s Comment 1).Results: Research productivity followed a triphasic trajectory: a dormant phase (1986– 2000, ≤ 2 articles/year), a stabilization phase (2001– 2014, +4% annual growth), and an exponential growth phase (2015– 2024, 13 articles/year), closely aligned with global policy shifts in traditional medicine. China emerged as the dominant contributor (338 articles, 64.2% global output), yet Canada demonstrated superior research impact (108 citations/article), highlighting a productivity-impact paradox. Mechanistic investigations into neuroimmunological pathways, particularly μ-opioid receptor modulation (centrality 0.74), became central research pillars, reinforced by biomarker-correlated clinical trials showing β-endorphin-FEV1 interactions (r = 0.526, p = 0.008). Persistent translational gaps were evident, with 63% of RCTs relying on subjective “deqi” assessments despite technological advances in objective acupuncture monitoring.Conclusion: This analysis reveals critical asymmetries between Eastern research productivity and Western methodological innovation in acupuncture-COPD research. This analysis suggests a need for a threefold strategy integrating multiscale neuroimaging validation, globalized trial standardization through CONSORT-Acupuncture frameworks, and equitable North-South knowledge exchange to address the growing burden of COPD-related dyspnea in aging populations. Keywords: acupuncture, COPD, bibliometrics, neuroimmunology, research disparities, traditional medicine